Exploring the Begarap Tradition in Shaping Character and Social Integrity in Sasak Society - Pangga, Dwi; Ahzan, Sukainil; Suryati, Suryati; Sutajaya, Made; Suja, Wayan; Astawa, Ida Bagus Made (Reflection Journal, 2024)
This study explores the role of the Begarap tradition in shaping character and maintaining social integrity within the Sasak community in Lombok. The primary objective is to understand how Begarap functions as a conflict resolution mechanism and social control tool in the face of modernization challenges. The research employs a qualitative approach, combining literature studies and in-depth interviews with traditional and religious leaders in Pujut and Praya Timur. The findings reveal that Begarap remains relevant in upholding values of honesty and social responsibility. This ritual carries strong spiritual elements, where individuals swear an oath using sacred water from Nyatuq’s grave. The belief in supernatural consequences enhances its effectiveness in regulating behavior. Despite social transformations due to globalization, Begarap endures as a symbol of cultural and religious identity. The study concludes that Begarap contributes significantly to maintaining social stability and reinforcing moral values within the Sasak community. Recommendations include integrating Begarap’s values into education and promoting its preservation through documentation and further research to ensure its relevance in the modern era.